Developing clinical grade flexible implantable electronics. (16th March 2023) - Liu, Yu; Balsamo, Domenico; Degenaar, Patrick
Abstract: Implantable electronic sensors and systems are utilised in an increasingly broad array of clinical applications, such as pacemakers, neuro-modulators and bioelectronic vagal nerve controllers. Advances in microelectronics, materials, and bio-interfaces allow for new clinical applications and support fundamental research. However, a longstanding issue with such devices has been the mismatch between the relative stiffness of such structures compared to tissue softness. This disparity has led to tissue rejection in the form of scar tissue around implantable probes, leading to loss of function and/or capability. This review, therefore, explores the field of implantable electronics and neuroprosthetics with a particular focus on developments in soft, flexible devices. We include advancements in materials and device topologies as well as the current understanding of their long-term efficacy in biological tissue.